Guided Writing Method with Picture Card Assistance on Third Grade Students’ Autonomous Learning in Descriptive Text Writing - Fitryadiningrum, G. A. Deby; Kristiantari, Maria Goreti Rini; Ambara, Didith Pramunditya (International Journal of Language and Literature, 2025)
Autonomous learning is an important attitude that students should have so that they do not depend on others and can be disciplined and responsible, especially in writing description text. Descriptive text aims to describe an object or event in writing. The low autonomous learning of elementary school students' writing skills is caused by the ineffective learning methods used. This study aims to determine the effect of the guided writing method assisted by picture cards on autonomous learning skills in writing description text. The research used a quantitative approach of quasi-experimental type with a non-equivalent control group design. The study population was third-grade elementary school students in Gugus VI Gianyar in the 2024/2025 school year. The sample of 49 students was selected using the cluster random sampling technique. Data were collected using a questionnaire and analyzed by independent sample t-test. The results of the analysis showed tcount 6.832 > ttable 2.012. Thus, H₀ is rejected, and Hₐ is accepted. In conclusion, the guided writing method assisted by picture cards effectively improves autonomous learning of students' description text writing skills. This study expands the understanding of how incremental learning combined with visual aids can enhance autonomous learning and expressive ability in young learners. In addition, this study provides teachers with replicable and student-centred teaching strategies suitable for implementation in real classrooms.